Cognitive Correlates of Improvised Behaviour in Disaster Response: the Cases of the Murrah Building and the World Trade Center. (1st July 2014) - Mendonça, David; Webb, Gary; Butts, Carter; Brooks, James
<x xml:space="preserve">Abstract</x> While emergency response actions are known to range from conventional to improvised, less is known about the thinking processes that underlie these actions. This paper presents a statistical analysis of cognition and behaviour reported by police personnel who responded to two significant US disasters: the 1995 bombing of the Murrah Building in Oklahoma City and the 2001 attack on the World Trade Center in New York City. The results suggest the prominence of conventional behaviour coupled with cognitive processes closely tied to recognition, and of improvised behaviours that are linked to more explicit reasoning processes. The results underscore the value of exploring cognitive foundations of both conventional and improvised behaviours to enrich understanding of human response to disaster.